2017
DOI: 10.1007/s00221-017-5138-6
|View full text |Cite
|
Sign up to set email alerts
|

Fall risk during opposing stance perturbations among healthy adults and chronic stroke survivors

Abstract: Studies examining recovery from SLIPS and TRIPS indicate higher incidence of falls during SLIPS than TRIPS however, differences in the recovery mechanisms during these opposing perturbations have not been examined. We therefore aimed to compare the reactive balance responses contributing to fall risk during SLIPS and TRIPS at comparable perturbation intensity among community-dwelling healthy adults and chronic stroke survivors. Younger adults (N = 11), age-matched adults (N = 11) and chronic stroke survivors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The FRT distance of the participants with stroke were 7.79% lower than that of healthy adults and the SLART distance was 24.52% lower. These results are similar to previous research findings, which suggested that it is difficult for patients with chronic stroke to secure stability in a static and dynamic balanced environment when compared with young adults and healthy adults of similar age [39].…”
Section: Discussionsupporting
confidence: 92%
“…The FRT distance of the participants with stroke were 7.79% lower than that of healthy adults and the SLART distance was 24.52% lower. These results are similar to previous research findings, which suggested that it is difficult for patients with chronic stroke to secure stability in a static and dynamic balanced environment when compared with young adults and healthy adults of similar age [39].…”
Section: Discussionsupporting
confidence: 92%
“…8A), we found that the stick perturbations had a stronger scaling effect than slip perturbations for the same increment (from 0.2 to 0.4). Backward instability created by belt decelerations (stick perturbations) tend to be more challenging than forward instability created by the belt accelerations (slip perturbations) (Patel and Bhatt 2018; Roeles et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations during walking can induce potential losses of balance and elicit corrective locomotor adaptations, which are useful for understanding human balance control (Mansfield et al 2015; Torres-Oviedo et al 2011). There are multiple approaches to perturb gait stability, including split-belt walking (Buurke et al 2018; Torres-Oviedo et al 2011), visual flow distortions (Franz et al 2016; O’Connor and Kuo 2009), waist pulling (Hof et al 2010; Vlutters et al 2018), platform displacements (Afschrift et al 2018; McIntosh et al 2017), and rapid changes in treadmill belt speed (Debelle et al 2020; Patel and Bhatt 2018). Studies using discrete perturbations such as waist pulling, platform displacements, and changes in treadmill belt speeds often apply the perturbation once out of every 5-20 strides (Afschrift et al 2018; Debelle et al 2020; Hof et al 2010; McIntosh et al 2017; Patel and Bhatt 2018; Vlutters et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the FSLR showed that a longer stance phase was associated to the identification of patients (OR = 1.547). The trunk kinematics was also reported as fundamental for the upright balance during walking in patients with stroke, being exposed to the risk of fall ( 23 , 24 ). The inertial measurement of trunk kinematics during walking is probably the most important factor associated to this dynamic balance ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%